PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA BELAJAR MENURUT KI HAJAR DEWANTARA PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN - Alin Salassa’; Risna Rombe; Rani Rani; Nurlita Nurlita; Jenri Fani Parinding (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Differentiated learning has become a crucial aspect in the implementation of the Free Learning Curriculum, developed with inspiration from the thoughts of Ki Hajar Dewantara. The focus on learning that takes into account individual differences in learning styles, pace, and needs is essential in creating an inclusive and relevant learning experience. This article discusses the application of the concept of Differentiated Learning in the curriculum of the subject of Christian Religious Education. With the backdrop of Ki Hajar Dewantara's progressive views, this study analyzes how the principles of the Free Learning Curriculum, such as granting learning freedom and personalized learning, can be integrated into Christian Religious Education. Through a qualitative approach, this research involves literature study and analysis of methods, strategies, and implementation of learning that considers individual differences in the context of Christian religious education. The results of the analysis show that the implementation of Differentiated Learning in the subject of Christian Religious Education results in a more inclusive and adaptive learning environment. Varied teaching methods and the use of diverse materials provide space for students with different learning styles to achieve deeper understanding. Granting learning freedom allows students to explore their faith personally, while individual support aids students with special needs in achieving learning goals. This research demonstrates that Differentiated Learning in Christian Religious Education can enhance teaching effectiveness, accommodate student diversity, and facilitate the achievement of optimal learning outcomes in line with the principles of the Free Learning Curriculum.